The Effects of an Ocular Direct Electrical Stimulation on Pattern-Reversal Electroretinogram - Blum, Maren-Christina; Hunold, Alexander; Solf, Benjamin; Klee, Sascha (Frontiers in Neuroscience, 2020)
Studies on transcranial current stimulation have shown that a direct current stimulation of the occipital cortex can influence the amplitude size of a visual evoked potential (VEP). The current direction (cathodal or anodal) determines whether the VEP amplitudes increase or decrease. The aim of this study was to design a new experimental setup that will enable a simultaneous ocular direct current stimulation and electroretinogram (ERG) recording which will broaden our understanding of current stimulation effects on the visual system. Furthermore, we examined whether a direct current stimulation on the eye has a similar effect on an electroretinogram (ERG) as on a VEP. The pattern-reversal ERG was measured with sintered Ag/AgCl skin-electrodes, positioned on the lower eyelid (active), the earlobe (reference), and the forehead (ground). Direct current was applied through a ring rubber electrode placed around the eye and a 5 cm x 5 cm rubber electrode placed at the ipsilateral temple with a current strength of 500 µA and a duration time of 5 min. Fifty-seven healthy volunteers were divided into three groups depending on the current direction (cathodal, anodal, and sham stimulation, n = 19 each). One ERG measurement (ERG 1) was performed before and another (ERG 2) during the direct current stimulation. The difference between ERG 1 and ERG 2 measurements for the characteristic P50, N95 and N95’ (N95 minimum measured from zero line) amplitudes were evaluated by both confidence interval analysis and t-test for related samples (α = 0.05, after Bonferroni correction p* = 0.0055). The P50 amplitude was significantly decreased for ERG 2 measurement in the cathodal and anodal stimulation group (cathodal p = 0.001, anodal p = 0.000). No significant changes could be found in the N95 and N95’ amplitudes as well as in the sham-stimulation group. Additionally, the latencies did not undergo any significant changes. In conclusion, the newly designed experimental setup enables simultaneous current stimulation and ERG recording. The current influenced P50 amplitude although not the N95 and N95’ amplitudes. Furthermore, the amplitude size decreased for both current directions and did not lead to contrary effects as expected.